Beta endorphin release in patients after spontaneous and provoked acute myocardial ischaemia. Issue 3 (March 1992) - Oldroyd, K G; Harvey, K; Gray, C E; Beastall, G H; Cobbe, S M
Abstract : BACKGROUND--In animal models of circulatory shock and heart failure concentrations of the endogenous opioid peptide beta endorphin are raised and opioid receptor blockade improves haemodynamic variables and survival. This study was performed to identify whether acute myocardial ischaemia provokes the release of beta endorphin in humans. METHODS--Observational study in a university cardiology centre. Serial measurements of beta endorphin made by specific radioimmunoassay were correlated with other clinical and neuroendocrine variables that were measured prospectively. Fifty five patients with acute myocardial ischaemia and 26 patients undergoing elective coronary angioplasty of the left anterior descending coronary artery were studied. RESULTS--beta endorphin concentrations were raised above the upper limit of normal in 31/42 (74%) patients with confirmed myocardial infarction, 3/13 (23%) patients with unstable angina, and 10/24 (42%) patients after coronary angioplasty. There was no evidence of myocardial release of beta endorphin. There were significant positive correlations between beta endorphin and the concentrations of adrenocorticotrophic hormone, cortisol, and arginine vasopressin. In patients with acute myocardial ischaemia there was a significant positive correlation between the peak concentrations of creatine kinase and beta endorphin but no correlation with visual analogue scores of the intensity of chest pain. The highest beta endorphin concentrations were seen in patients whose clinical course was complicated by the development of heart failure. CONCLUSIONS--beta endorphin release is a component of the neuroendocrine activation associated with myocardial ischaemia/infarction.